THE QUALITY OF WINTERWHEAT GRAIN DEPENDING ON SOWING TIME AND FERTILIZATION - Astakhova, Ya. V. (Scientific Progress & Innovations, 2020)
The results of three-year research in the Northern Steppe concerning the influence of sowing time and mineral nutrition on biochemical properties of grain of soft winter wheat varieties (Lastivka Odeska and Ho-lubka Odeska) and hard wheat (Burshtyn) on weed-free fallow and after spring barley are presented in the article. Winter wheat was sown in three periods - September 7, September 22 and October 7. Fertilization variants were the following: 1 – without applying fertilizers (control); 2 – pre-sowing applying fertilizers (on weed-free fallow - N30P60K30, after spring barley – N60P60K30); 3 – fertilization system (against the back-ground of pre-sowing applying mineral fertilizers on weed-free fallow, additional fertilization at the end of plant tillering stage - N30 locally, after spring barley – N30 on frozen-thawed soil + N30 locally). It has been found that in most variants of the experiment a higher content of protein, crude gluten in the grain and better sedimentation indices among the soft wheat varieties were observed in Lastivka Odeska variety. For Lastivka Odeska and Burshtyn varieties, no clear influence of sowing time on these indices was found. As for Holubka Odeska variety, against all fertilization backgrounds after the stubble predecessor, the largest amount of protein and gluten in grain was formed in the early sowing time (September 7). When sowing in the later periods (September 22 and October 7) these indices naturally decreased. It has been revealed that grain of Burshtyn hard winter wheat variety, in contrast to winter soft varieties, contained more protein and gluten in all fertilization variants. On the whole, the amount of protein in Lastivka Odeska varied on weed-free fallow in the range of 11.99–13.58 %, Holubka Odeska – 11.02–12.62, and in Burshtyn variety – 12.93–14.61 %. After spring barley these indices made 11.47–13.43, 10.68–12.42 and 11.92–14.53 %, respectively. But grain of hard wheat was characterized by low flour sedimentation indices, and gluten was more extensible and weaker than gluten of soft wheat varieties. It has been determined that the maximum values of grain quality indices for all winter wheat varieties were observed at fertilization system, which provided nitrogen additional fertilization of crops in the spring plant vegetation period against the background of pre-sowing application of mineral fertilizers .